Response to “Meaningful Motivation for Work Motivation Theory” - Steers, Richard M.; Mowday, Richard T.; Shapiro, Debra L. (Academy of Management Review, 2005)
This article presents a response by Richard M. Steers, Richard T. Mowday and Debra L. Shapiro to Christopher Michaelson's comments on the July 2004 “Academy of Management Review” Special Topic Forum regarding the Future of Work Motivation Theory. Steers and colleagues agree with Michaelson that the articles in the forum did not directly address his desire to see further linkages developed between work motivation theories and people's legitimate desire for meaningful lives. The authors note that no papers were submitted to this special issue directly examining the topic and encouraged Professor Michaelson to develop this linkage. If there are to be any future papers on the subject the line of theory development will need to be differentiated from current constructs in work motivation research which currently focus on intrinsic sources of motivation.